PREVALENCE OF POST-OPERATIVE WOUND INFECTIONS AMONG ORTHOPEDICS PATIENTS WITH SURGICAL IMPLANT TERTIARY CARE HOSPITAL - Abdul Rauf Tippu; Muhammad Ishfaq Mazari; Muhammad Shahnawaz Ahmad; Muhammad Usman Faisal; Naveed Shamsheer Mughal; Rasheed Ahmed Bhatti (Journal of Ayub Medical College Abbottabad, 2024)
Background: Germs may infect an injured site via the tissues when the host’s systemic and local defenses are compromised. Pus discharge may be a sign of a significant wound infection, requiring a follow-up operation to ensure sufficient draining. Additionally, generalized symptoms may appear, and returning home may need to be postponed. Objective was to identify the prevalence of post-operative wound infections among orthopedics patients with surgical implant tertiary care hospitals. Method: A cross-sectional study was conducted at a tertiary care hospital from July 2023 to December 2023, involving 180 patients with closed long bone fractures. The patients were immune-competent, not diabetic, and older than 10 years. All patients underwent surgery using implants, with general anesthesia and a third-generation cephalosporin prophylactic antibiotic. Patients were monitored monthly for 6 months to monitor infection symptoms. Cultures were obtained from wound discharges, and patients experienced perioperative fever for two days following surgery. Data was collected and analyzed using the SPSS 22 version. The study aimed to improve the management of bone fractures. Results: A total of 180 patients were selected for the current study including both males (65.60 %) and females (34.4 %) with closed fractures. Most of them were above 31 years of age, furthermore, 20.5 % and 24.4 % of them were 41-50 as well as above 60 years of age. 13 (7.22 %) of them had developed them post-operatively. 0.76 % had pre-operative stays in the hospital for more than 10 days. Staphylococcus aureus was the most frequent 5 (38.6 %) bacteria. 6 (46.15 %) were managed by frequent irrigation along with 4 (30.76 %) by the administration of antibiotics. Conclusion: Post-operative infection is one most troublesome complication among implanted patients. in the current the prevalence of post-op infection is 7.22 % which is comparable in developing nations, but far higher than that in developed countries. As a result, it should be managed with early detection and treatment, as well as by eradicating the prevalent causes of wound infections following surgery that the present research identified.